Ψ-Stability of Nonlinear Volterra Integro-Differential Systems with Time Delay. (2nd May 2013) - Li, Lianzhong; Han, Maoan; Xin Xue,; Liu, Yuanyuan
Abstract : We give some sufficient conditions for Ψ -uniform stability of the trivial solutions of a nonlinear differential system and of nonlinear Volterra integro-differential systems with time delay.